ISLAM DAN KESUSASTRAAN JAWA - Sururin; Muslim, Moh. (Direktorat Jenderal Bimbingan Masyarakat Islam, 2018)
This article is presented to study Javanese literary opuses. Javanese literature reached its peak during the Mataram Kingdom, significantly around 1688 to 1744. There are various literary opuses that emerged at the time, including those containing Islamic teachings, one of them tells that the teaching about mysticism was more dominant than any other fields. Stories about of manunggaling kawulo gusti (Javanese culture has its own characteristics). Islamic titles, for example, are carried by rulers, Islamic symbols are attached to their companions, and Islamic attributes are embroidered in their emperor?s clothes. However, such symbols do not seem to change their life and views point. Consequently, it is not so surprising if the term of Javanese Islam or Islam Kejawen appears. Artikel ini disajikan untuk mempelajari karya sastra Jawa. Sastra Jawa mencapai puncaknya selama Kerajaan Mataram, secara signifikan sekitar tahun 1688 hingga 1744. Ada berbagai karya sastra yang muncul pada saat itu, termasuk yang mengandung ajaran Islam, salah satunya mengatakan bahwa ajaran tentang mistisisme lebih dominan daripada bidang lainnya. Cerita tentang manunggaling kawulo gusti (budaya Jawa memiliki karakteristik tersendiri). Judul-judul Islam, misalnya, dibawa oleh para penguasa, simbol-simbol Islam melekat pada teman-teman mereka, dan atribut-atribut Islam disulam dalam pakaian kaisar mereka. Namun, simbol semacam itu tampaknya tidak mengubah cara hidup dan sudut pandang mereka. Konsekuensinya, tidak mengherankan jika istilah Jawa Islam atau Islam Kejawen muncul.